Engineering and functionalization of the disulfide-constrained miniprotein Min-23 as a scaffold for diagnostic application - Zoller, Frederic; Schwaebel, S. Thimon; Haberkorn, Uwe; Mier, Walter (ChemMedChem, 2012)
Miniproteins are scaffolds for the development of alternative non-immunoglobin binding agents for medical applications. This peptide format features high tolerance to sequence mutagenesis, excellent proteolytic stability, and fast blood pool clearance. Herein we present the total chemical synthesis of the disulfide-constrained scaffold Min-23 and its functionalization for in vitro and in vivo application. Optimized solid-phase peptide chemistry and oxidative folding strategies were developed to engineer this miniprotein with native-like disulfide configuration. High levels of serum stability and proteolytic resistance, as well as a beneficial pharmacokinetic profile for diagnostic imaging, were determined by using radiolabeling techniques such as positron emission tomography. The reported achievements highlight Min-23 as a promising scaffold for the development of novel recognition molecules for medical application.